can some one show me how to do this problem

negative four times the sum of n and seven is equal to negative five times n minus nine

Results 1 to 2 of 2

- Apr 16th 2006, 10:40 PM #1

- Joined
- Mar 2006
- Posts
- 14

- Apr 17th 2006, 12:09 AM #2

- Joined
- Nov 2005
- From
- someplace
- Posts
- 14,972
- Thanks
- 5

Originally Posted by**jim1174**

$\displaystyle

(-4)(n+7)=(-5)(n-9)

$

Multiply both sides of the equation by $\displaystyle -1/4$, and as

a "-" times a "-" is a "+" this gives:

$\displaystyle

n+7=(5/4)(n-9)

$

Now expand the brackets on the Right Hand Side of the equation:

$\displaystyle

n+7=\frac{5}{4}n-\frac{45}{4}

$

Add 45/4 to both sides of the equation:

$\displaystyle

n+\frac{73}{4}=\frac{5}{4}n

$.

Subtract $\displaystyle n$ from both sides:

$\displaystyle

\frac{73}{4}=\frac{1}{4}n

$.

Finlay multiply both sides by 4:

$\displaystyle

73=n

$,

so $\displaystyle n=73$

RonL